The trouble with STEAM and why we use it anyway - Mejias, Sam; Thompson, Naomi; Sedas, Raul Mishael; Rosin, Mark; Soep, Elisabeth; Peppler, Kylie; Roche, Joseph; Wong, Jen; Hurley, Mairéad; Bell, Philip; Bevan, Bronwyn (Science education (Salem, Mass.), 2021)
As an emerging field of theory, research, and practice, STEAM (Science, Technology, Engineering, Arts, and Mathematics) has received attention for its efforts to incorporate the arts into the rubric of STEM (Science, Technology, Engineering, and Mathematics) learning. In particular, many informal educators have embraced it as an inclusive and authentic approach to engaging young people with STEM. Yet, as with many nascent fields, the conceptualization and usage of STEAM is somewhat ambivalent and weakly theorized. On the one hand, STEAM offers significant promise through its focus on multiple ways of knowing and new pathways to equitable learning. On the other hand, it is often deployed in theory, pedagogy, and practice in ambiguous or potentially problematic ways toward varying ends. This paper attempts to disentangle some of the key tensions and contradictions of the STEAM concept as currently operationalized in educational research, policy, and practice. We pay particular attention to the transformative learning potential supported by contexts where STEAM is conceptualized as both pedagogical and mutually instrumental. That is, neither STEM nor arts are privileged over the other, but both are equally in play. We link the possibilities suggested by this approach to emerging theories for understanding how designing for and surfacing epistemic practices linked to the relevant disciplines being integrated into STEAM programs may point the way toward resolving tensions in inter‐ and transdisciplinary learning approaches.